Environmental Degradation in BRI Countries: Navigating the Role of Natural Resources, Green Energy and Green Finance - Asghar, Muhammad Muzammil; Arshad, Zavish; Yousaf, Shehzad; Ali, Muhammad Sibt e; Tariq, Muhammad (Pakistan Journal of Humanities and Social Sciences, 2024)
This study examines the role of natural resources, green energy and green finance in influencing environmental degradation using the data of 105 BRI countries from 2001 to 2021. For data analysis, different panel data estimation approaches, i.e., cross-sectional dependence tests, slope homogeneity tests, panel cointegration tests, FGLS and PCSE models, and DH causality tests, are used. The outcomes of CIPS and CADF tests display that the variables ED, GDP, NR, and GF are stationary at level, whereas GE and TR are stationary at I(1). The Westerlund and Pedroni cointegration tests confirm the long-run cointegration in a model. Furthermore, the FGLS model validates the EKC framework in BRI countries. The findings also show that green energy and green finance are critical for reducing CO2 emissions in BRI countries. The study also shows that natural resources are augmenting the CO2 emissions in BRI countries. Therefore, based on the study outcomes, it is concluded that BRI countries should promote green finance and green energy to enhance environmental quality.